A novel performance measure for characterising efficient immunisation strategies in computer networks and populations. (2017) - Safaei, Farshad; Pakravan, Iman; Akbar, Reza; Rahimkhani, Maryam
In this paper, an efficient immunisation strategy is devised for different types of networks, ranging from peer-to-peer computer networks to scale-free and small-world social networks. This strategy, named I-ring (I-chain), is proposed in order to immunise the random acquaintance between the independent nodes. As long as the data flow is not halted by failures, they are routed minimally through the network. However, if the information flow is blocked by failures, the routing restrictions may be relaxed by rerouting the message flow such that it bypasses the failed nodes and faulty region. The proposed strategy requires no knowledge of node degrees or general information about the network and its topology. Most importantly, a novel performance measure is evolved to assess the reliability and robustness of networks, that is the probability of messages facing the I-ring (I-chain). The experimental results of simulations testify the accuracy and practicability of the proposed measure.